2018
DOI: 10.1086/695529
|View full text |Cite
|
Sign up to set email alerts
|

Auctions versus Posted Prices in Online Markets

Abstract: Auctions were very popular in the early days of internet commerce, but today online sellers mostly use posted prices. We model the choice between auctions and posted prices as a trade-o¤ between competitive price discovery and convenience. Evidence from eBay …ts the theory: auctions are favored by less experienced sellers and for idiosyncratic products, and auction listings sell at a discount but with higher probability relative to comparable posted price listings. We then show that the decline in auctions was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(84 citation statements)
references
References 21 publications
3
75
0
2
Order By: Relevance
“…Crowdfunding and peer-to-peer lending are in the ascendant. A variety of literature has made efforts to delve into the forms of crowdfunding, such as an equity purchase, loan, or pre-order on a product [48][49][50][51][52], or the economic mechanisms of peer-to-peer lending [15,[53][54][55]. For example, Wei and Lin [15] both theoretically and empirically investigated how the supply and demand of funds in online peer-to-peer lending markets are matched, and the prices at which transactions will occur.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Crowdfunding and peer-to-peer lending are in the ascendant. A variety of literature has made efforts to delve into the forms of crowdfunding, such as an equity purchase, loan, or pre-order on a product [48][49][50][51][52], or the economic mechanisms of peer-to-peer lending [15,[53][54][55]. For example, Wei and Lin [15] both theoretically and empirically investigated how the supply and demand of funds in online peer-to-peer lending markets are matched, and the prices at which transactions will occur.…”
Section: Related Literaturementioning
confidence: 99%
“…They concluded that, under platform-mandated posted prices, loans are funded with high probability, but at the same time with relatively high preset interest rates. Einav et al [55] showed that the choice between auctions and posted prices in online markets is essentially a trade-off between competitive discovery and convenience. Moreover, Gong [20] systematically analyzed the current situation, future prospect, and possible economic mechanisms of Internet finance, and the potential links between the use of the Internet and credit availability in China.…”
Section: Related Literaturementioning
confidence: 99%
“…Aliens have to pay for accessing the community network (as they do not contribute APs) through, for example, purchasing Wi-Fi passes from the operator. 3 Another important tool for dealing with problems with incomplete information is auction theory [22], which has also been widely-used in wireless networks [23][24][25]. Auction is more useful for the scenario of allocating limited resources among a set of users with incomplete (asymmetric) information, while contract is more useful for the scenario of motivating different types of users (with private information) behave in a desired way.…”
Section: System Modelmentioning
confidence: 99%
“…Note that the right-hand side of (28) might have multiple solutions, hence the dual function d(λ) may not be differentiable. We apply the subgradient method to solve the dual problem (27), i.e., we update the dual variable according to (22) in Algorithm 1, where t is the iteration index. The update rule (22) is intuitive: the dual variable λ k increases if the constraint p k ≤ p k+1 is violated.…”
mentioning
confidence: 99%
“…Hertzberg et al (2016) studies borrowers' choices in online markets but focuses on adverse selection on loan maturity. Related to our focus on auctions, Einav et al (2016) examine auction theory in the context of eBay. Most relevant for our paper, Wei and Lin (Forthcoming) use Prosper's elimination of auctions to test a model of auction pricing.…”
Section: Introductionmentioning
confidence: 99%